mHealth Innovation in Asia Grassroots Challenges and Practical Interventions - Baulch, Emma; Watkins, Jerry; Tariq, Amina (Mobile Communication in Asia: Local Insights, Global Implications, 2018)
This book offers a detailed account of a range of mHealth initiatives across South, Southeast and East Asia. It provides readers with deep insights into the challenges such initiatives face on the ground, and a view of the diverse cultural contexts shaping strategies for overcoming these challenges. The book brings together various discussions on the broader mHealth literature, and demonstrates how a research focus on diverse Asian contexts influences the success and/or failure of current mHealth initiatives. It also highlights the important roles social scientists can play in advancing theoretical approaches, as well as planning, implementing and evaluating mHealth initiatives. The book is a valuable resource for project planners, policy developers in NGOs and government institutions, as well as academics, researchers and students in the fields of public health, communications and development studies. This book is open access under a CC BY license.